Climate-smart livestock nutrition in semi-arid Southern African agricultural systems - Fushai, Felix; Chitura, Teedzai; Oke, Oyegunle Emmanuel (Frontiers in Veterinary Science, 2025)
Climate change is disrupting the semi-arid agricultural systems in Southern Africa, where livestock is crucial to food security and livelihoods. This review evaluates the bioenergetic and agroecological scope for climate-adaptive livestock nutrition in the region. An analysis of the literature on climate change implications on livestock nutrition and thermal welfare in the regional agroecological context was conducted. The information gathered was systematically synthesized into tabular summaries of the fundamentals of climate-smart bioenergetics, thermoregulation, livestock heat stress defence mechanisms, the thermo-bioactive feed components, and potentially climate-smart feed resources in the region. The analysis supports the adoption of climate-smart livestock nutrition when conceptualized as precision feeding combined with dietary strategies that enhance thermal resilience in livestock, and the adaptation of production systems to the decline in availability of conventional feedstuffs by incorporating climate-smart alternatives. The keystone potential climate-smart alternative feedstuffs are identified to be the small cereal grains, such as sorghum (Sorghum bicolor) and pearl millet (Pennisetum glaucum) as dietary energy sources, the native legumes, such as the cowpea (Vigna unguiculata) and the marama bean (Tylosema esculentum) as protein sources, wild browse Fabaceae trees such as Vachellia spp. and Colophospermum mopane, which provide dry season and drought supplementary protein, minerals, and antioxidants, the non-fabaceous tree species such as the marula tree (Sclerocarya birrea), from which animals consume the energy and electrolyte-rich fresh fruit or processed pulp. Feedstuffs for potential circular feeding systems include the oilseed cakes from the macadamia (Macadamia integrifolia) nut, the castor (Ricinus communis), and Jatropha (Jatropha curcas) beans, which are rich in protein and energy, insect feed protein and energy, primarily the black soldier fly larvae (Hermetia illucens), and microbial protein from phototrophic algae (Spirulina, Chlorella), and yeasts (Saccharomyces cerevisiae). Additives for thermo-functionally enhanced diets include synthetic and natural anti-oxidants, phytogenics, biotic agents (prebiotics, probiotics, synbiotics, postbiotics), and electrolytes. The review presents a conceptual framework for climate-smart feeding strategies that enhance system resilience across the livestock-energy-water-food nexus, to inform broader, in-depth research, promote climate-smart farm practices and support governmental policies which are tailored to the agroecology of the region.